In Vivo Measurement of Glenohumeral Joint Contact Patterns. (19th August 2009) - Bey Bey, Michael J. Michael J.; Kline Kline, Stephanie K. Stephanie K.; Zauel Zauel, Roger Roger; Kolowich Kolowich, Patricia A. Patricia A.; Lock Lock, Terrence R. Terrence R.
Abstract : The objectives of this study were to describe a technique for measuring in-vivo glenohumeral joint contact patterns during dynamic activities and to demonstrate application of this technique. The experimental technique calculated joint contact patterns by combining CT-based 3D bone models with joint motion data that were accurately measured from biplane x-ray images. Joint contact patterns were calculated for the repaired and contralateral shoulders of 20 patients who had undergone rotator cuff repair. Significant differences in joint contact patterns were detected due to abduction angle and shoulder condition (i.e., repaired versus contralateral). Abduction angle had a significant effect on the superior/inferior contact center position, with the average joint contact center of the repaired shoulder 12.1% higher on the glenoid than the contralateral shoulder. This technique provides clinically relevant information by calculating in-vivo joint contact patterns during dynamic conditions and overcomes many limitations associated with conventional techniques for quantifying joint mechanics.